2013
DOI: 10.3109/0886022x.2013.867799
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant effects of maslinic acid in livers, hearts and kidneys of streptozotocin-induced diabetic rats: effects on kidney function

Abstract: Studies indicate that hyperglycemia-induced oxidative stress triggers the development of microvascular and macrovascular complications in diabetes. Accordingly, we hypothesized that maslinic acid (MA) prevents these complications due to its antioxidant properties. We, therefore, investigated the effects of 5-week MA treatment of streptozotocin (STZ)-induced diabetic rats on anti-oxidative status of cardiac, hepatic and renal tissues as well as on kidney function. Proximal tubular effects of MA were studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 46 publications
4
76
2
Order By: Relevance
“…Various medicinal plant extracts have been reported to significantly reduce food intake possibly through the reduction of plasma ghrelin levels (Bast et al, 2002;Fong, 2002). Studies conducted in our laboratory have shown that Syzygium aromaticum-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose concentrations in STZ-induced diabetic rats in sub-chronic studies through a variety of mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014;Musabayane et al, 2010;Ngubane et al, 2011). Furthermore, these triterpenes have previously been reported to reduce food intake through unknown mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Various medicinal plant extracts have been reported to significantly reduce food intake possibly through the reduction of plasma ghrelin levels (Bast et al, 2002;Fong, 2002). Studies conducted in our laboratory have shown that Syzygium aromaticum-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose concentrations in STZ-induced diabetic rats in sub-chronic studies through a variety of mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014;Musabayane et al, 2010;Ngubane et al, 2011). Furthermore, these triterpenes have previously been reported to reduce food intake through unknown mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Studies conducted in our laboratory have shown that Syzygium aromaticum-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose concentrations in STZ-induced diabetic rats in sub-chronic studies through a variety of mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014;Musabayane et al, 2010;Ngubane et al, 2011). Furthermore, these triterpenes have previously been reported to reduce food intake through unknown mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014). This study was therefore designed to evaluate the effects of these triterpenes on plasma ghrelin concentrations as well as the gastrointestinal expression of this hormone.…”
Section: Introductionmentioning
confidence: 99%
“…8 Our study shows that transdermal PI matrix patches can reverse the previously reported inability of the kidney to excrete Na + in STZ-diabetes mellitus. [30][31][32] Hyperinsulinemic edema and hypertension associated with intensive insulin therapy have been attributed, at least in part, to Na + retaining action of insulin. 8 However, literature evidence on the effects of insulin on kidney function in diabetes is conflicting and remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that S . aromaticum -derived oleanolic acid (OA) and maslinic acid (MA) possesses anti-inflammatory, antibacterial, antioxidant, and hepatoprotective properties [1619]. We, therefore, speculate that these plant extracts may exert antiplasmodial effects against P .…”
Section: Introductionmentioning
confidence: 99%